Digital democracy - An analysis of the potential of digital technologies as a factor strengthening a civic culture - Lima, Andreia Lucimar Silva de; Silva, Juliana Santos da; Medeiros, Liziany Muller; Tybusch, Jerônimo Siqueira (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Lately it has been possible to observe a growing interest in the field of digital technologies bound specifically to the development of new political practices and actions, e.g., the approximation between citizens and their political representatives, the onset of a more active participation in political decisions and the possibility of access to information, amongst others. The objective of this paper is to demonstrate that through existing digital technologies, and amongst them a few will be described, it should be possible to accomplish a critical diagnosis on the potentialities and the challenges that arise at this new phase of democracy. It is expected that while developing a reflection on digital democracy and the existing fragility in communication over the internet there will be created a space/ambience with potential for mediation of this recent civic culture that is being established in this country. The herein adopted methodology was the procedure of literature review, taking in account as basic theory the writings of Lévy, Castells, Carvalho, Lorencini, Gaggiano, among others. In the social dimension, the level was found to be moderate, but inspiring care about the poor records of HDIM, high rates of illiteracy and infant mortality. The economic dimension, it seems, requires more urgent action, as it reached the maximum level of vulnerability in all indicators, namely: low per capita income, low number of employees in the formal sector, low agricultural production and GDP inexpressible.